A two-dimensional type I superionic conductor - Rettie, Alexander J. E.; Ding, Jingxuan; Zhou, Xiuquan; Johnson, Michael J.; Malliakas, Christos D.; Osti, Naresh C.; Chung, Duck Young; Osborn, Raymond; Delaire, Olivier; Rosenkranz, Stephan; Kanatzidis, Mercouri G. (Nature materials, 2021)
Superionic conductors possess liquid-like ionic diffusivity in the solid state, finding wide applicability from electrolytes in energy storage to materials for thermoelectric energy conversion. Type I superionic conductors (for example, AgI, Ag 2 Se and so on) are defined by a first-order transition to the superionic state and have so far been found exclusively in three-dimensional crystal structures. Here, we reveal a two-dimensional type I superionic conductor, α-KAg 3 Se 2 , by scattering techniques and complementary simulations. Quasi-elastic neutron scattering and ab initio molecular dynamics simulations confirm that the superionic Ag + ions are confined to subnanometre sheets, with the simulated local structure validated by experimental X-ray powder pair-distribution-function analysis. Finally, we demonstrate that the phase transition temperature can be controlled by chemical substitution of the alkali metal ions that compose the immobile charge-balancing layers. Our work thus extends the known classes of superionic conductors and will facilitate the design of new materials with tailored ionic conductivities and phase transitions. Superionic conductors present liquid-like ionic diffusivity with applications ranging from energy storage to thermoelectrics. A two-dimensional type I superionic conductor α-KAg 3 Se 2 is now reported and should help to design other materials with tailored ionic conductivities and phase transitions.